2021
DOI: 10.1371/journal.pntd.0009312
|View full text |Cite
|
Sign up to set email alerts
|

Use of seroprevalence to guide dengue vaccination plans for older adults in a dengue non-endemic country

Abstract: A shift in dengue cases toward the adult population, accompanied by an increased risk of severe cases of dengue in the elderly, has created an important emerging issue in the past decade. To understand the level of past DENV infection among older adults after a large dengue outbreak occurred in southern Taiwan in 2015, we screened 1498 and 2603 serum samples from healthy residents aged ≥ 40 years in Kaohsiung City and Tainan City, respectively, to assess the seroprevalence of anti-DENV IgG in 2016. Seropositiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Another newer dengue vaccine candidate, which was developed by Takeda, was found to be efficacious and safe in both dengue-naïve and dengue-exposed adults and children in the recently concluded clinical trial [ 51 , 52 ]. Therefore, DENV seroprevalence study is important for evidence-based recommendations in guiding dengue vaccine implementation [ 28 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another newer dengue vaccine candidate, which was developed by Takeda, was found to be efficacious and safe in both dengue-naïve and dengue-exposed adults and children in the recently concluded clinical trial [ 51 , 52 ]. Therefore, DENV seroprevalence study is important for evidence-based recommendations in guiding dengue vaccine implementation [ 28 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 demonstrates the relative DIC values to the best model for the 31 data sets. The results show that the best model for data sets [ 23 , 24 , 25 , 26 , 28 , 29 , 32 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 ] is Model C. In addition, Model C is also applicable to the data sets of 2012 and 2013 in the Guangzhou study [ 27 ] and the data sets from August to November 2015 and from August to September 2017 in the Kaohsiung study [ 43 ]. The best model for 25 data sets among the 31 data sets is Model C: constant FOI is broken by a critical age.…”
Section: Resultsmentioning
confidence: 99%
“…Since a wider age group may not accurately reflect the difference in the seropositivity rate of the age group [ 19 ], the studies that had at least five age groups were included. Based on these selection criteria ( Figure 1 ), 23 studies [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were finally included ( Supplementary File S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…To address the needs of public health services and stakeholders for DENV and ZIKV vaccines, active community-based surveillance tools are needed that can provide accurate estimates of disease burden, identify risk factors, and be performed quickly and with limited resources. 9,12,13 Rapid cross-sectional seroprevalence surveys, paired with appropriate diagnostic testing, may serve as one such costeffective tool. Recent reviews found that existing DENV and ZIKV seroprevalence studies demonstrate significant heterogeneity in their methodology and often introduce selection bias due to a lack of probabilistic sampling.…”
Section: Introductionmentioning
confidence: 99%